1996
DOI: 10.1111/j.1365-2222.1996.tb00589.x
|View full text |Cite
|
Sign up to set email alerts
|

Function and regulation of FcεRI expression on monocytes from non‐atopic donors

Abstract: Monocytes from both atopic donors and healthy individuals express Fc epsilon RI, but the previously reported different expression levels between the two groups seem to be directly related to the absence or presence of IgE in the serum. This may be due to the fact that Fc epsilon RI is subjected to a constant turnover process which is slowed down but not prevented by ligand binding. In addition, free Fc epsilon RI on non-atopic monocytes are under control of a neuramindase sensitive structure(s), which influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…On these cells, however, the lack of β–chain protein from the FcεRI complex is held responsible for structural and functional differences [2, 3]. The recent establishment of FcεRI–expressing human monocytic cell lines [4, 5] allows for the confirmation of experiment results, obtained in the ‘classical’ FcεRI model, the rat basophilic leukemia cell.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…On these cells, however, the lack of β–chain protein from the FcεRI complex is held responsible for structural and functional differences [2, 3]. The recent establishment of FcεRI–expressing human monocytic cell lines [4, 5] allows for the confirmation of experiment results, obtained in the ‘classical’ FcεRI model, the rat basophilic leukemia cell.…”
Section: Introductionsupporting
confidence: 53%
“…The generation of the FcεRI–α expression vector was described before, as was the transfection by electroporation [4]. Cell labeling was performed as previously described [4]. Measurements included isotype controls and a viability measurement with 7–aminoactinomycin D and were analyzed on a FACScan (Becton Dickinson, Calif.) equipped with ‘Lysis II’ version 1.0 software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results have demonstrated that phosphate–buffered saline (PBS) stabilised monocyte surface expression of FcεRI, CD14 and CD64, measured by FACS analysis of cell surface receptors as previously described [2]. PBS caused a cycloheximide–insensitive, significant increase in surface FcεRI, arguing against de novo receptor synthesis, while CD14 and CD64 remained stable [2]. The logical conclusion drawn from these results was that a component present in the conventional culture media RPMI and IMDM, but absent from PBS, was responsible for FcεRI down–regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Although β–message has been reported in monocytes, the signal has not yet been verified on the protein level. It is known that this structural variation accounts for differences in signal transduction, due to the lack of the signal–amplifying β–chain [1], and it is possibly responsible for the reduced FcεRI receptor stability on the surface of monocytes [2]. …”
Section: Introductionmentioning
confidence: 99%